1969
DOI: 10.1055/s-0038-1651390
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of the Stable Plasminogen Activator of the Venous Wall in Occlusion Induced Fibrinolytic State

Abstract: SummaryThe fibrinolytic activity respectively the PA activity of normal veins before and after venous occlusion is measured by the histochemical method of Todd. The results show marked decreases of PA of the adventitia and an increase of PA of the endothelial type, after venous occlusion. This suggests a transfer of PA through the venous wall into the intravascular lumen, and may be the cause of increased fibrinolytic activity in venous blood after occlusion. Contrary assumptions are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

1970
1970
1984
1984

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…In a previous study on venous occlusion in humans it was found that 20 min of stasis produced a shift in PA activity from the adventitial to the intimal layer (15). In our study no such signs were detected.…”
Section: Discussioncontrasting
confidence: 56%
“…In a previous study on venous occlusion in humans it was found that 20 min of stasis produced a shift in PA activity from the adventitial to the intimal layer (15). In our study no such signs were detected.…”
Section: Discussioncontrasting
confidence: 56%
“…
Venous occlusion seems to be a potent stimulus to provoke an enhancement of fibrinolytic activity in plasma and in venous endothelium, 2,3,4,5,6,7 In addition Ogston et a1.8 reported on a significantly increased plasminogen activator of the venous blood compared with the arterial blood. Therefore we tried to elucidate the role of tissue activator of the arterial wall in experimental arterial occlusion.
METHODS

Five adult full grown rabbits weighing 2.5 to 3.5 kg were used.

…”
mentioning
confidence: 99%
“…This assay method has proved useful in comparison of the fibrinolytic activity of human veins of arms and legs in healthy persons and patients with thrombosis (11 , 12, 13). The same principle, but modified, has been used by other authors to assess the fibrinolytic activity of veins (3,4) and of the prostata (7).…”
Section: Resultsmentioning
confidence: 99%